2018
DOI: 10.22543/7674.52.p218229
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy lifestyle and the risk of metabolic syndrome - the Romanian experience

Abstract: Background. Metabolic syndrome (MetS) represents a clustering of metabolic risk factors for cardiovascular disease. Many studies have shown the influence of an unhealthy lifestyle on the risk of MetS, yet some aspects remain controversial. Aim of the study: to investigate the relationship between an unhealthy lifestyle and the risk of MetS. Materials and Methods. The study was conducted using a sample of 181 patients, 54 (29.8%) males and 127 (70.2%) females, aged 59.95±10.8 years. The baseline survey involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
1
8
0
2
Order By: Relevance
“…Cozma and colleagues stated that living in rural areas is a major risk factor for MetS. 46 Noshad and colleagues also showed that MetS and all is individual components were significant by area of living, with more significant difference in subjects living in urban areas, 38 which was in accordance with results of our study. the mild difference between the results of these two studies may be contributed to urbanization of Iran as well as diet modification in both urban and rural areas, 50 which significantly affect the frequency of abdominal obesity and subsequently other components of MetS.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Cozma and colleagues stated that living in rural areas is a major risk factor for MetS. 46 Noshad and colleagues also showed that MetS and all is individual components were significant by area of living, with more significant difference in subjects living in urban areas, 38 which was in accordance with results of our study. the mild difference between the results of these two studies may be contributed to urbanization of Iran as well as diet modification in both urban and rural areas, 50 which significantly affect the frequency of abdominal obesity and subsequently other components of MetS.…”
Section: Discussionsupporting
confidence: 92%
“…27 A number of previous studies also revealed a reverse association between lower educational level and risk of MetS. 46,47 Ha et al reported that subjects with high school education or higher were less likely to develop three or four components of MetS compared with those with high school and primary school education. 48 In contrast, a study conducted on Chinese adults showed that CVD risk factors are more prevalent in high-income families with high educational level.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many studies have shown conflicting results regarding the impact of the metabolic syndrome on AF development, with some suggesting that AF is rather linked to some components of the metabolic syndrome rather than to the metabolic syndrome itself (5). The metabolic syndrome, defined as the co-occurrence of several metabolic risk factors in a single patient, can be easily diagnosed in a routine check-up and it is a common finding among Romanian patients, some studies reporting a prevalence >65% (7).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is associated with atherosclerosis in cardiovascular diseases, Alzheimer's disease, type-2 diabetes mellitus, and metabolic syndrome (13). The incidence of metabolic syndrome is continually increasing, because of unhealthy lifestyle changes in the general populationan increasing consumption of fast foods, high-fat diets and processed foods, a sedentary life style, and lack of physical exercise (14).…”
Section: Obesity and Nash Pathogenesismentioning
confidence: 99%